2018
DOI: 10.5455/msm.2018.30.294-296
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy of Erosion of Cervix and Low Grade Squamous Intraepithelial Lesion

Abstract: Introduction: Cervical erosion and squamouse intraepithelial lesion of low grade are most common gynecological problems of women. These changes on cervix are cause of painful coitus and enhanced vaginal secretion. Cryotherapy is widely accepted method in treating these changes and sympthoms. Aim: The aim of this study is to examine the efficiency of cryotherapy in eliminating erosion of cervics and LSIL, as well as conditions following these states. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…17,18 There are many bodies of evidence that support the effectiveness of this method in curing the symptoms of cervical ectropion. 3,[19][20][21] In the study by Yildiz et al, cryotherapy had a positive impact on the improvement of vaginal discharge, post-coital bleeding, and pelvic pain, which confirmed our findings. 3 Another study showed the highest success rate of cryotherapy in women with abundant leukorrhea but the lowest in women with recurrent cervicitis, and pelvic pain.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…17,18 There are many bodies of evidence that support the effectiveness of this method in curing the symptoms of cervical ectropion. 3,[19][20][21] In the study by Yildiz et al, cryotherapy had a positive impact on the improvement of vaginal discharge, post-coital bleeding, and pelvic pain, which confirmed our findings. 3 Another study showed the highest success rate of cryotherapy in women with abundant leukorrhea but the lowest in women with recurrent cervicitis, and pelvic pain.…”
Section: Discussionsupporting
confidence: 91%
“…After this treatment, the ablated tissue becomes crusty and the process of re‐epithelialization begins 17,18 . There are many bodies of evidence that support the effectiveness of this method in curing the symptoms of cervical ectropion 3,19–21 . In the study by Yildiz et al., cryotherapy had a positive impact on the improvement of vaginal discharge, post‐coital bleeding, and pelvic pain, which confirmed our findings 3 .…”
Section: Discussionsupporting
confidence: 85%
“…It must be considered that there is no difference in persistence of symptoms between inflammatory group and LSIL (CIN 1) group, as observed by Jahic et al 22 Similar findings were also found in a study done by Katakdhond et al and Jahic et al 4,22 Mohanty et al recorded that cryotherapy eliminates enhanced vaginal secretion and pain in 98% 12 weeks after the treatment. 16 The efficacy of present study is 91.9% and is comparable with most studies.…”
Section: Resultssupporting
confidence: 68%
“…Size of lesion and location of lesion distribution described in Table 1. 4,[13][14][15][16] In another study conducted by Patil et al abnormal vaginal discharge was found in 55% of patients and this disparity might be because of different prevalence in the institute where the study was conducted. 17 Hence, abnormal white discharge was the main indication of cryotherapy among all patients.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical carcinoma can be prevented successfully if the preceding changes like atypical (ASC-H) and squamous lesions of high grade (HSIL) are discovered in time. It is considered that it takes around 10 years in order for a low grade lesion to develop into cervical carcinoma, although in practice it comes to a faster development of this carcinoma ( 6 ). Cytology and colposcopy are used for screening of cervical carcinoma, whereas a definitive diagnosis is concluded based on pathohistological findings i.e.…”
Section: Introductionmentioning
confidence: 99%